MODELING RISK MEASUREMENT IN EMERGING MARKET - Asri, Marselinus (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2021)
Purpose – This study aims to make modeling measurement risk in capital market variables. Design/methodology/approach – Using Mathematical approaches to integrated a noticeable increase in the ﬁrm-level idiosyncratic risk, the volatility measure of coeficient is greater and has a stronger upward trend than the new idiosyncratic volatility measure. Findings – Using the the model decomposing total risk in market variance extended by Bali et.al, we integrated the model with initial model, Fama-French idiosyncratic risk Model, we sugested new model: Rit -RFt = ai + bi (R Mt R Ft) + var.HLt+ var.SBt +Var.MW +Var.RW+ Var.CMA + ei Originality – This paper introduces a variance measure of aggregate idiosyncratic risk, which does not require estimation of market betas or correlations and is based on the concept of gain from portofolio diversification. Keywords: Idiosyncratic Risk, New Model Paper Type Research Result